ضغوط العمل وعلاقتها بالرضا الوظيفي ودافعية الإنجاز لدى معلمي المهارات الحياتية في سلطنة عمان - ظفرية، سعادة هاشل سليم (Kulliyah of Education, International Islamic University Malaysia, 2021)
The main objective of this study was to investigate work stress and its relationship to job satisfaction and achievement motivation among Life Skills teachers in basic education schools in the Sultanate of Oman. To achieve the objectives of the study, the researcher used descriptive methods, which covered both quantitative and qualitative. The data were collected by the researcher using two methods: questionnaires, as the main method, and semi-structure interviews as a confirmatory method. The study sample consisted of 313 male and female teachers of Life Skills subject. A stratified random sampling method was used to choose a sample of 306 male and female teachers to answer the questionnaires, while by using purposive sampling, seven male and female teachers were selected for interviews including 4 female teachers and 3 male teachers. For quantitative data, arithmetical means, standard deviation, MAVOVA, Pearson correlation and stepwise regression analysis were used for the analysis. For qualitative data, content analysis was used to analyze the interviews. The main results of the study revealed that Life Skills teachers experiencing work stress that ranged from moderate to high level. Work stress that was at the high level in the questionnaire was related to society, parents, income and work system, whereas the work stress at the high level in the interviews was related to students, classroom environment, evaluation and teaching methods. In addition, the results indicated that teachers' job satisfaction was at the moderate level and motivation was at the high level. The results also showed that there was a reverse negative statistically significant correlation between the level of work stress and job satisfaction. Moreover, there was a weak negative correlation but not statistically significant between the level of work stress and the level of motivation achievement. The study concluded with a number of recommendations, the most significant were as follows: the necessity of educating parents and society about the importance of Life Skills curriculum in inculcating citizenship values and promoting/strengthening moral ethics and attitudes; increasing the number of Life Skills teachers as a solution for the multiple curriculums and the high density of students; and involving Life Skills teachers in decision making when making any changes or modifications related to Life Skills curriculum.